Leader Identity and Coordination - Sonia R. Bhalotra; Irma Clots-Figueras; Lakshmi Iyer; Joseph Vecci (Institute of Labor Economics (IZA), 2018)
This paper examines the effectiveness of leaders in addressing coordination failure in societies with ethnic or religious diversity. We experimentally vary leader identity in a coordination game and implement it in the field across 44 towns in India. We find that religious minority leaders (Muslims) improve coordination, while majority leaders (Hindus) do not. We test the effectiveness of intergroup contact and affirmative action, two commonly used policies to improve the well-being of minorities. Intergroup contact improves coordination irrespective of leader identity, but affirmative action leads to deterioration in coordination in Muslim-led groups alongside an increase in coordination in Hindu-led groups. We find that both policies are less effective for Muslim-led groups in towns with a recent history of religious conflict. Our findings contribute novel evidence to research on coordination failure, leader identity, policy alternatives for promoting integration of minorities, and conflict.
Keywords: P16; D70; D91; J78; 330; coordination failure; leader identity; leader effectiveness; religion; affirmative action; intergroup contact; conflict; India